Experimental investigation of pore structure and its influencing factors of marine-continental transitional shales in southern Yan’an area, ordos basin, China - Hui Xiao; Hui Xiao; Hui Xiao; Nan Xie; Nan Xie; Yuanyuan Lu; Tianyue Cheng; Tianyue Cheng; Wei Dang; Wei Dang (Frontiers in Earth Science, 2022)
The intensive study of the pore structure and its controlling factors of shale reservoir has important guiding significance for further exploration and exploitation of shale gas. This work investigated the effects of organic and inorganic compositions on the development of pore structures of the Upper Permian Shanxi shale in the southern Yan’an area, Ordos Basin. Based on the results of high-pressure mercury intrusion, low-pressure N2 and CO2 adsorption and organic geochemical experiments, X-ray diffraction and scanning electron microscope observations, the mineral composition, pore structure and its influencing factors of the transitional shale were studied systematically. The results indicate that the total organic carbon (TOC) content of the shale is between 0.12% and 5.43%, with an average of 1.40%. The type of the organic matter (OM) belongs to Type III and has over maturity degree with an average Ro of 2.54%. An important character of this kind of shale is the large proportion of clay mineral content, which ranges from 40.70% to 87.00%, and with an average of 60.05%. Among them, illite and kaolinite are the main components, and they account for 36.6% and 36.7% of the total clay minerals respectively, followed by chlorite and illite/smectite (I/S) mixed layer. The quartz content is between 10.6% and 54.5%, with an average of 35.49%. OM (organic matter) pores are mostly circular bubble-shaped pores, and most of them are micropores, while inorganic pores are well developed and mainly contributed by clay mineral pores and have slit-type, plate-like and irregular polygon forms. Mesopores are the major contributor to pore volume (PV), while micropores contribute the least to PV. The contribution of micropores to the specific surface area (SSA) is greater than 61%, followed by mesopores. Macropores have almost no contribution to the development of SSA. OM pores are the main contributor to the total specific surface area of the shale, with an average contribution rate of 61.05%, but clay mineral pores contribute more to the total pore volumes. In addition, both the content of chlorite and illite/smectite (I/S) mixed layer is positively correlated with the volume ratio of mesopores. It was found that high TOC, I/S mixed layer and chlorite content are all favorable conditions for the target shale.